The Role of L-type Calcium Channels in Olfactory Learning and Its Modulation by Norepinephrine - Ghosh, Abhinaba; Carew, Samantha J.; Chen, Xihua; Yuan, Qi (Frontiers in Cellular Neuroscience, 2017)
L type calcium channels (LTCCs) are prevalent in different systems and hold immense importance for maintaining/performing selective functions. In the nervous system, CaV1.2 and CaV1.3 are emerging as critical modulators of neuronal functions. Although the general role of these calcium channels in modulating synaptic plasticity and memory has been explored, their role in olfactory learning is not well understood. In this review we first discuss the role of LTCCs in olfactory learning especially focusing on early odor preference learning in neonate rodents, presenting evidence that while NMDARs initiate stimulus-specific learning, LTCCs promote protein-synthesis dependent long-term memory. Norepinephrine release from the locus coeruleus is essential for early olfactory learning, thus noradrenergic modulation of LTCC function and its implication in olfactory learning is discussed here. We then address the differential roles of LTCCs in adult learning and learning in aged animals.